Dipole-Driven Charge Trapping in Monolayer Janus MoSSe for Ultrathin Nonvolatile Memory Devices - Ko, Eun Bee; Sung, Junho; Choi, Seon Yeon; Hassan, Yasir; Bae, Jeong‑Ju; Kim, Jongseok; Kim, Hyun You; Lee, Eunho; Choi, Min Sup; Kim, Hyun Ho (Nano-Micro Letters, 2026)
The continued scaling of flash memory technologies faces challenges such as limited operation speed, poor data retention, and interface defects inherent to conventional three-dimensional architectures. Two-dimensional (2D) materials, with van der Waals interfaces and atomic-scale thickness, offer a promising pathway to overcome these limitations by enabling efficient charge modulation while minimizing surface defects. In this work, a nonvolatile 2D flash memory device is developed employing monolayer Janus MoSSe as the charge-trapping layer and hexagonal boron nitride (h-BN) as an ultrathin tunneling barrier. The intrinsic structural asymmetry of Janus MoSSe induces a strong vertical dipole moment, resulting in enhanced charge trapping, deeper energy barriers, and directional polarization compared with symmetric 2D materials. Consequently, the devices exhibit outstanding retention times exceeding 104 s, endurance beyond 104 program/erase cycles, and large memory window ratios (ΔV/VG,max of 50%–70% for 10 and 6 nm h-BN, respectively), with charge-trapping rates up to 8.96 × 1014 cm−2 s−1. In addition, Janus MoSSe-based devices show synaptic characteristics under electrical pulses and perform recognition simulations in artificial neural networks. These findings establish a design paradigm for 2D memory devices, enabling ultrathin, flexible, and energy-efficient nonvolatile memories. Highlights: 1 Janus MoSSe-based floating-gate memory exhibits ultrafast charge-trapping dynamics and stable charge retention exceeding 108 s under low-voltage operation. 2 The intrinsic out-of-plane dipole moment in Janus MoSSe effectively suppresses leakage current and enlarges the memory window, even with ultrathin h-BN tunneling layers. 3 The proposed all-van der Waals heterostructure provides a scalable platform for high-speed, energy-efficient, and reliable nonvolatile memory applications.